Sensor for a Solid–Liquid Tribological System - Ruize Zhang; Zeyang Yu; Zhikai Fan; Shanshan Wang; Yihui Xiang; Yanfei Liu; Zhongnan Wang (Sensors)
Solid–liquid lubrication systems have been widely used to enhance tribological behaviors. Alongside offering exceptional lubrication and wear-resistance performance, the active control of the tribological behavior of lubrication systems in accordance with service conditions is equally critical. To achieve this goal, accurately monitoring the condition of the lubrication system is fundamental. This review article aims to provide a fundamental understanding of different sensors for monitoring the condition of lubricants, as well as the friction and wear properties. Specifically, the sensors suitable for engineering applications are detailed introduced. Through this review, we wish to provide researchers in mechanical engineering with a clear technical overview, which can guide the design of intelligent lubrication systems with suitable sensors.